2002
DOI: 10.1142/s0217979202012906
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependence of MR Fluids

Abstract: The rheological properties of MR fluids, MRF-132LD, are investigated under the steady shear and oscillatory shear for a range of operating temperatures from 20°C to 60°C. This was accomplished by using an advanced rheometer with the parallel-plate configuration. Under the steady shear, the Herschel–Bulkley model is used to model the rheology of the MR fluid. The corresponding parameters namely, τyd, K and n were determined at various temperatures, in an attempt to minimize the discrepancies between the experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…Actually, it was almost six times higher at the highest magnetic field (Figure ). Such a trend was maintained at higher temperatures, although a decrease of the yield stress with temperature was obtained (see Figure S1 of the Supporting Information), in agreement with previous works. …”
Section: Resultssupporting
confidence: 91%
“…Actually, it was almost six times higher at the highest magnetic field (Figure ). Such a trend was maintained at higher temperatures, although a decrease of the yield stress with temperature was obtained (see Figure S1 of the Supporting Information), in agreement with previous works. …”
Section: Resultssupporting
confidence: 91%
“…For this study, castor oil is used as the base fluid and its viscosity is known to decrease with increase in temperature. Li et al [64] also observed a decrease in yield stress with increase in temperature. They obtained the yield stress values by fitting their data to the Herschel-Bulkley model and since all three parameters in the model, namely yield stress, consistency index (which indicates the consistency of the fluid), and power law index (which gives the degree of shear thinning) depend on various factors like temperature, magnetic field, material properties etc, they evaluated each quantity at different temperatures for a particular field.…”
Section: Resultsmentioning
confidence: 87%
“…MR applications can experience temperature variation in service as a result of external and internal heating sources such as ambient atmospheric temperature, dissipated mechanical energy due to friction and damping, dissipated electrical energy due to electromagnetic circuit. Generally, the increased temperature is known to reduce the yield stress and the viscosity of conventional MRFs [39,40]. Evaluating the temperature dependence of the HVLP MRFs is important for practical MR application.…”
Section: Effect Of Temperaturementioning
confidence: 99%